Tone From the Top: The Role of the General Counsel in the Prevention of Harassment and Abuse in International Sports - Carska-Sheppard, Andrea; Ammons, Sarah (Frontiers in Sports and Active Living, 2021)
To prevent harassment and abuse in sports, the consensus is that an essential factor is “tone from the top” of the organization. It is key as a catalyst and sustainer of change, whether in the corporate or sports world. An organization's general counsel is one of the go-to top advisors for executive leadership regarding laws and regulations. Additionally, they serve as advisors for issues in other areas, such as public policy, ethical and legal risks, and human rights. With their leadership, general counsels can play a vital role in the prevention of harassment and abuse in an organization. The guidance and leadership of the general counsel should facilitate reviewing and strengthening of the organization's policies and procedures and other strategies helping to prevent and address issues of harassment and abuse. Legal issues become more complex the more global the organization, so more complex strategies are needed to tackle these issues successfully.